Tingkat Percaya Diri Atlet Sepak Bola dalam Menghadapi Pertandingan - Sin, Tjung Hauw (JURNAL FOKUS KONSELING, 2017)
Abstract: This study is a descriptive study aimed at identifying the confidence level of club X football athletes in Padang City in preparation for the match with a sample of 20 athletes. Instruments in this study using the Athletes confidence scale. Data were analyzed using descriptive analysis using percentage technique. A description of the research results found that the level of trust of soccer athletes, in general, are in the medium and high category. Judging from the aspect of self-confidence is located in the high category, the positive thinking aspect, in general, is in the category of being, on the aspects of utilizing the advantages, in general, are in the high category. This study illustrates the overall condition of confidence is more dominant in the medium and high category but still exist in the low and very low category. So it is expected to need optimization efforts confident athletes soccer team to play with more optimal at the next game. These efforts can be prepared personally or with the help of a dedicated professional who has psychological athletes psychological expertise such as motivators or sports counselors or specialized trainers who can contribute to improving athletes confidence.Keywords: Self Confidence, Soccer Match